Responses to the sovereignty/vulnerability/development dilemmas : small territories and regional organization in the CaribbeanTT - - Byron, Jessica (Centre de recherche sur les pouvoirs locaux dans la Caraïbe (Schoelcher, Martinique), 2013)
"The Americas have a rich history of regional cooperation. In the Caribbean Basin, however, mechanisms for regional cooperation and/or integration have emerged which have sought to transcend the issues of legal status and to address common questions of socio-economic development, democratic institutions and functions. Three regional grouping fall into this category: the Caribbean Community (1937), the Organization of Eastern Caribbean States (1981) and the Association of Caribbean States (1994). This paper will do a comparative survey and analysis of the three organizations. The second part of the paper will examine the specific areas of greatest participation by the non-independent members in the activities of specific regional organizations. The conclusion addresses contemporary themes such as the dynamics of political/constitutional evolution which affect the membership of non-independent territories."